Should prenatal care providers offer pregnancy options counseling? - Nancy F. Berglas; Valerie Williams; Katrina Mark; Sarah C. M. Roberts (BMC, 2018)
Abstract Background Professional guidelines indicate that pregnancy options counseling should be offered to pregnant women, in particular those experiencing an unintended pregnancy. However, research on whether pregnancy options counseling would benefit women as they enter prenatal care is limited. This study examines which women might benefit from options counseling during early prenatal care and whether women are interested in receiving counseling from their prenatal care provider. Methods At four prenatal care facilities in Louisiana and Maryland, women entering prenatal care completed a self-administered survey and brief structured interview (N = 586). Data were analyzed through descriptive statistics, bivariate analyses, multivariate multinomial logistic regression, and coding of open-ended responses. Results At entry into prenatal care, most women reported that they planned to continue their pregnancy and raise the child. A subset (3%) scored as having low certainty about their decision on the validated Decision Conflict Scale, indicating need for counseling. In addition, 9% of women stated that they would be interested in discussing their pregnancy options with their prenatal care provider. Regression analyses indicated some sociodemographic differences among women who are in need of or interested in options counseling. Notably, women who reported food insecurity in the prior year were found to be significantly more likely to be in need of options counseling (RRR = 3.20, p < 0.001) and interested in options counseling (RRR = 5.48, p < 0.001) than those who were food secure. Most women were open to discussing with their provider if their pregnancy was planned (88%) or if they had considered abortion (81%). More than 95% stated they would be honest with their provider if asked about these topics. Conclusions Most women are certain of their decision to continue their pregnancy at the initiation of prenatal care. However, there is a subset of women who, despite entering prenatal care, are uncertain of their decision and wish to discuss their options with their health care provider. Screening tools and/or probing questions are needed to support prenatal care providers in identifying these women and ensuring unbiased, non-directive counseling on all pregnancy options.